Leveling and Worship in Islamic Banking to Increase the Value - Aziz, Roikhan Mochamad; Falaach, Gilang Fajrul; Sen, Hasbi (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2023)
This study aims to analyze the level of reflexivity towards the merger activities of Islamic banks in Indonesia. The case studies that are the object of this study are 3 Islamic banks that have just merged. The data used in this study is secondary data sourced from financial reports issued by each Islamic bank or financial services authority. The measurement of this level of reflexivity uses bank performance values and Islamic values. This study aims to investigate the effect of various variables using multiple linear regression. The findings suggest that Hahslm has a reflective effect on both financial performance and worship. Additionally, it is suggested that the application of good prayer in Hahslm's activities contributes to the observed changes in these variables when comparing the results before and after to further analyze the results and understand the relationships between the variables, it would be helpful to know the specific independent variables included in the regression analysis. These independent variables could be factors related to Hahslm's operations, management practices, or any other relevant variables that might influence financial performance and worship. The use of multiple linear regression allows for the examination of the simultaneous impact of multiple independent variables on the dependent variables. By analyzing the regression coefficients, it is possible to determine the strength and direction of the relationships between the variables. This study will also look at the effect of variables using multiple linear regression.